Teaching Factory Management for Dressing, Catering, Beauty and SPA Program - Rahmadan Rahmadan; Muhammad Kristiawan; Rambat Nur Sasongko (AL-ISHLAH: Jurnal Pendidikan, 2022)
The goal of this research is to describe the areas of preparation, implementation, supporting and inhibiting factors for activities, as well as solutions to overcome the inhibiting factors for teaching factory management in the Superior Program of Competence in Clothing, Catering, and Beauty and SPA Expertise Competence Programs at a vocational high school in Bengkulu City, Academic Year 2021/2022. This study is a qualitative descriptive of the management teaching factory program, which excels in the competitive abilities of Dressing, Catering, Beauty, and SPA. The respondents were six teachers of a Vocational School in Bengkulu City. The findings revealed that management is effective in accordance with the management program that has been established. This paper provides all vocational school stakeholders with concerns on factory management where they would have excellent competence of the student.